Diagnosis of Sodic Conditions in Saline-Alkali Soils of Western Rajasthan - Kolarkar, A S; Singh, N (Annals of Arid Zone, 2016)
An attempt has been made to find out the relationships -between: (i),pH of soil and the ESP status (ii) SAR of soil paste extract and ESP in the saline and alkali soils of western Rajasthan. Highly significant correlations exist between these characters nd hence could be used for rapid appraisal of ESP status in saline and sodic soils. An adaptability of the equation given by U.S. Salinity Laboratory to find out ESP from SAR has also been considered. Depending on correlation coefficient and the coefficient of dotermination pH : ESP relation stands first, equation given by U.S. Salinity Laboratory second and SAR :ESP relation the third.